“A Game We All Play”: Identity, Epistemology, and Transformation in Undergraduate Psychology Students - Yuan, James Y.; Tafarodi, Romin W. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2026)
The epistemological commitments of any scientific discipline are reflected in the changing beliefs and identities of its students. Challenges to psychology’s scientific legitimacy presented by the recent replication crisis have underscored the need for critical and reflexive pedagogical perspectives in the discipline. This study aims to capture undergraduate psychology students’ changing views of their area of study, and what these changes suggest about tensions within the discipline. Interviews of first-year and fourth-year psychology students at the University of Toronto were analyzed using reflexive thematic analysis. Results show that the fourth-years, though more conversant with academic psychology’s values and commitments than their younger peers, were more troubled by issues pertaining to ethical and epistemological validity. Fourth-years also reported feelings of alienation and disenfranchisement due to their practical powerlessness to address theoretical issues of which they were critically aware. The results suggest a loss of confidence in psychology’s claims to knowledge, as well as a need for pedagogical change. Creating space in the curriculum and lab culture for reflexively critical inquiry and transformative perspectives would help mitigate the alienation and frustration expressed by many students.